A Model Reference Adaptive Controller based Flamingo Search Algorithm for Liquid Level Control in Non-Linear Conical Tank System - Selvaraj S. P.; Thiyagarajan R.; Rajavenkatesan T (Measurement Science Review, 2025)
Conical tanks (CTs) play a vital role in the process industry as they can prevent residues in the tank. On the other hand, liquid level controlling in a CT is a complicated process due to the non-linear cross-sectional area. The complexity in CTs is also increased by the limitation to manipulated variables, interactions in measurements, and frequent disturbances. The control of liquid levels in CTs is of great importance in the process industry. In this paper, the model reference adaptive control (MRAC) with the modified proportional integral derivative (MPID) controller is proposed to maintain the liquid level at the set points. Two proportional integral derivative (PID) controller blocks are used in the proposed MRAC. The controller parameters are tuned using flamingo search optimization algorithm (FSA) based on minimum mean square error (MSE). The proposed method is implemented in MATLAB/Simulink platform and the results are considered with respect to different set points and disturbance conditions. Also, the results are compared with the existing controllers such as proportional integral (PI), PID, fractional-order proportional integral (FOPI) and MRAC-PID. The results show that the proposed MRAC provides lower integral square error (ISE) and integral absolute error (IAE) values of 38.25 and 2167, respectively.